KARAKTER MORFOLOGI BUAH EMPAT JENIS PISANG (Mussa spp) LOKAL ASAL INDRAGIRI HULU - Devi Mayawi Isna; Mardaleni; Putri Lukmanasari (DINAMIKA PERTANIAN, 2024)
Riau is home to a wealth of genetic resources distributed across various regions, including local banana varieties found in Indragiri Hulu. A study titled "Morphological Characteristics of Four Types of Bananas (Mussa spp)" was conducted from September to November 2023 to explore the morphological traits and shelf life of these local bananas. The study involved designing research parameters, collecting data through field identifications and observations, and analyzing the data using the STAR and DMRT applications at a 5% significance level. Kinship relationships were assessed using the MVSP 32 application with the UPGMA method, analyzed through NTSys-pc 2.1 software, with results presented in a dendrogram format. The study observed nine qualitative and eight quantitative morphological characteristics. The dendrogram revealed that the four local banana varieties from Indragiri Hulu could be grouped into two main clusters. The first group includes Banten, Kepok, and Lilin bananas, displaying a 50% similarity based on traits such as fruit shape, cross-section, and skin color before and after ripening. The second group consists of a single variety: Kepok bananas. Notably, Kepok and Banten bananas exhibited closer similarities based on characteristics such as fruit weight per fruit, the number of fruits per bunch, and fruit length. Overall, these four banana types exhibit diversity in traits related to the number of fruits per bunch and the thickness of the fruit skin.